Efficacy evaluations of Mimosa pudica tannin isolate (MPT) for its anti-ophidian properties - Ambikabothy, J.; Ibrahim, H.; Ambu, S.; Chakravarthi, S.; Awang, K.; Vejayan, J. (Elsevier, 2011)
Aim of the study: Evaluations of the anti-snake venom efficacy of Mimosa pudica tannin isolate (MPT) obtained from root of the plant. Materials and method: MPT was investigated in vitro and in vivo for its efficacy against the venom of Naja kaouthia snake. Results: In vitro: (1) mice injected i.p. with MPT pre-incubated with Naja kaouthia venom at concentrations as low as 0.625 mg/ml showed 100% survival after a 24-h observation period. (2) In the proteomics study, mice injected with MPT pre-incubated with the Naja kaouthia venom showed down-regulation of five serum proteins. (3) In the protein–dye-binding study, the percentage of Bradford dye–protein binding showed a reduction relative to the decrease in MPT concentration used to incubate with the venom. In vivo: the results from the animal studies showed that MPT had no in vivo protection against the Naja kaouthia venom (0.875 mg/kg) in four different rescue modes and in an oral pre-treatment experiment. Conclusion: The study indicated the promising ability of MPT to neutralize the Naja kaouthia venom in in vitro experiments but fell short in its in vivo potential. As such, the use of Mimosa pudica (Mimosaceae) as therapeutics for snake bites is questionable as all the possible in vivo rescue studies and pre-treatment of the active constituents showed no protection against the affected mice.